A novel zero-dimensional steady-state model of a Stirling engine with inter-chamber mass transfer - Fernanda Graeff Silverio; Luís Mauro Moura; Stephan Hennings Och (Case Studies in Thermal Engineering)
Stirling engines are gaining renewed interest for industrial and transport applications due to their ability to convert waste heat into mechanical or electrical energy. This study presents a novel zero-dimensional steady-state model of a β-type Stirling engine that includes inter-chamber mass transfer between two synchronized units—a feature absent in conventional models. Unlike CFD-based simulations, the proposed model remains computationally efficient while capturing the performance impact of variable mass conditions. During the high-volume isochoric phase, a valve allows the working fluid to shift from the engine undergoing isothermal compression to the one performing isothermal expansion, increasing power output. The model is based on helium and validated using the GPU-3 engine geometry against a baseline without mass transfer. Simulation results show up to a 34% increase in net work and a 9% gain in thermal efficiency at a compression ratio of 1.5 with a 2.5 g charge mass. The engine can operate at source temperatures as low as 500 K with just 1.5% mass transfer. Increasing the charge mass boosts power output, while regenerator effectiveness significantly affects efficiency. Overall, the findings demonstrate that controlled mass transfer combined with efficient regeneration can meaningfully enhance Stirling engine performance under realistic conditions.